Recursive Integral with Fuzzy Control Method used in Shunt Hybrid Active Power Filter - Zhao, Wei; Chen, Ruimin; Luo, An (Energy procedia, 2012)
A current control method for a shunt hybrid active power filter (HAPF) using recursive integral algorithm is presented in this paper. The method improves performance of the HAPF system by reducing the influence of detection accuracy, time delay of instruction current calculation and phase displacement of output filter. Fuzzy logic based set-point weighing algorithm is combined in the control scheme to enhance its robustness and anti-interference ability. The proposed algorithm is easy for engineering application and has small computation capacity. Experiment results have verified the validity of the proposed controller. Furthermore the proposed recursive integral PI algorithm can also be applied in the control of periodic current as in AC drivers.